Controlled Friction Behaviors of Porous Copper/Graphite Storing Ionic Liquid through Electrical Stimulation. Issue 5 (11th December 2017) - Zhang, Guoliang; Xie, Guoxin; Wang, Jie; Si, Lina; Guo, Dan; Wen, Shizhu; Yang, Fan
Abstract : Porous copper/graphite composites storing stimuli‐responsive lubricant can be used to fabricate a new kind of electrical contact friction materials. However, the synergetic lubricating effect of solid and liquid lubricants incorporated into the copper matrix is rarely discussed. In this work, neat copper and its composites storing ionic liquids (ILs) have been successfully prepared via a template‐free strategy. The effect of frictional, electrical, and electro‐frictional coupling stimulation on the tribological behavior of the copper filled with graphite has been investigated using ball‐on‐disk friction tests. Results show that a high voltage may accelerate the release of the ILs stored in the composite to the friction interface, thereby resulting in a low coefficient of friction (COF) (ca. 0.14) at the voltage of 0.5 V, which is superior to those of the pure copper without applying voltage. The COF is more stable in copper/graphite composite storing ILs (SI) than in copper‐SI. Therefore, the graphite efficiently protects the surface of the sample from wear and electrochemical corrosion. Abstract : The ionic liquids (ILs) stored in the pores of the copper matrix respond to the frictional, electrical, and electro‐frictional coupling stimulation has been investigated using ball‐on‐disk friction tests under external electric fields. A proper voltage may accelerate the release of the ILs to the friction interface, thereby resulting in a low coefficient of friction.